The Effect of Talent Management and Knowledge Management on Employee Performance with Job Satisfaction as Mediation in the Yogyakarta Special Region Government - Hafizh Susilo; Winarno Winarno; Khoirul Hikmah (Journal of Business Innovation and Research, 2022)
This study aims to analyze the effect of talent management and knowledge management on employee performance mediated by job satisfaction for Civil Servants in the Yogyakarta Special Region Government. Employee performance is thought to be influenced by the management of human resources, namely talent management and knowledge management with job satisfaction. This study uses a quantitative approach with data collection through questionnaires. The population of this research is the Civil Servants of the Yogyakarta Special Region Government who have received Education and Cadre Training of 60 employees with the sunsus technique in sampling. The analytical method used in this research is Path Analysis. The results of the study indicate that talent management and knowledge management have a direct and significant effect on employee performance. Talent management has an indirect effect on employee performance mediated by job satisfaction. Knowledge management has an indirect effect on employee performance mediated by job satisfaction.